PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. SUPRAPRIMATAMA NUSANTARA JAKARTA - Muhammad Sularno; Dini Handrini (Sekolah Tinggi Manajemen IMMI, 2019)
The purpose of this study was to determine the effect of the work environment on employee performance at PT. Supra Primatama Nusantara, Jakarta.“Data analysis methods and techniques used in this research is quantitative analysis to be able to determine the effect of the work environment on employee performance at PT. Supra Primatama Nusantara, Jakarta. Respondents in this study were 78 respondents. The method in this study uses data collection methods, sampling using saturated sampling and analysis using validity tests, reliability tests, correlation coefficient tests, coefficients of determination, simple regression analysis and hypothesis testing.“From the results of the calculation of the influence of the work environment on employee performance based on the calculation of the correlation coefficient, a value of 0.718 means that the influence of the work environment on employee performance can be categorized as having a very strong influence. From the calculation of the coefficient of determination (KD) obtained a value of 0.515, this shows that the contribution of the work environment to employee performance is 51.5%, while the remaining 48.5% is influenced by other factors. Furthermore, the results of hypothesis testing show that there is an influence of the work environment on employee performance, this is based on a hypothesis test that can be concluded with a value of tcount ttable that is 8.990 ttable 1.992, in this case Ho is rejected and Ha is accepted there is a significant influence between the work environment on the performance of employees at PT. Supra Primatama Nusantara, Jakarta.